2016
DOI: 10.1002/ejsp.2179
|View full text |Cite
|
Sign up to set email alerts
|

Legitimate lies: The relationship between omission, commission, and cheating

Abstract: Across four experiments, we show that when people can serve their self-interest, they are more likely to refrain from reporting the truth (lie of omission) than actively lie (lie of commission). We developed a novel online “Heads or Tails” task in which participants can lie to win a monetary prize. During the task, they are informed that the software is not always accurate, and it might provide incorrect feedback about their outcome. In Experiment 1, those in the omission condition received incorrect feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
1
11
1
Order By: Relevance
“…We did not find a significant tendency for participants to engage more in corruption when it involved passive actions in comparison with active ones. This result does not support reports that omissions which result in negative outcomes are considered more acceptable than acts of commission that cause the same outcomes (Bar-Eli et al, 2007;Kordes-de Vaal, 1996;Pittarello et al, 2016;Spranca et al, 1991). It also contradicts the claim of Tenbrunsel and Messick (2004) which suggests that dishonest behaviors that take more passive forms are considered more acceptable compared to the ones that take more active formsand the works of Bar-Eli et al (2007), Kordes-de Vaal (1996), Pittarello et al(2016), and Spranca et al, (1991) which reported that there is a tendency of judging omission as less severe than comission upon causing negative outcomes.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…We did not find a significant tendency for participants to engage more in corruption when it involved passive actions in comparison with active ones. This result does not support reports that omissions which result in negative outcomes are considered more acceptable than acts of commission that cause the same outcomes (Bar-Eli et al, 2007;Kordes-de Vaal, 1996;Pittarello et al, 2016;Spranca et al, 1991). It also contradicts the claim of Tenbrunsel and Messick (2004) which suggests that dishonest behaviors that take more passive forms are considered more acceptable compared to the ones that take more active formsand the works of Bar-Eli et al (2007), Kordes-de Vaal (1996), Pittarello et al(2016), and Spranca et al, (1991) which reported that there is a tendency of judging omission as less severe than comission upon causing negative outcomes.…”
Section: Discussioncontrasting
confidence: 73%
“…This tendency of judging inactions as less severe than actions in causing negative outcomes is a consistent phenomenon across several domains (Bar-Eli et al, 2007;Kordes-de Vaal, 1996;Pittarello et al, 2016;Spranca et al, 1991). In fact, individuals are more likely to refrain from telling the truth than actively lying when they face the temptation to benefit from dishonesty (Pittarello et al, 2016). This happens because there is reluctance in individuals to assign responsibility when dishonesty takes the form of omission if compared to the commission.…”
Section: Group Identity Amount Of Money and Type Of Actionmentioning
confidence: 77%
See 1 more Smart Citation
“…A key observation in our work is the existence of ethical free riders-people who intentionally benefit from others' rule-violating behavior without violating rules themselves. This observation resonates with work on passive cheating (also known as lying by omission), showing that individuals refrain from correcting mistakes made by a computer or another person as long as those mistakes are beneficial to them (Pittarello, Rubaltelli, & Motro, 2016). Whereas ethical free riding and passive cheating are similar in terms of profiting from not taking an action, ethical free riding goes beyond tolerating mistakes (caused by nature or another person) and indicates that people will also tolerate others' intentional rule violations.…”
Section: Discussionsupporting
confidence: 62%
“…Action-effect and omission-bias were originally framed as cognitive biases, yet people also seem to use these biases strategically and in sense-making. In interpersonal interactions, people aim to reduce accountability and mini- An example of the omission strategy is that people would rather refrain from reporting the truth than actively lie, in order to avoid condemnation and responsibility if caught (Pittarello, Rubaltelli, & Motro, 2016), yet if there is evidence for deliberate withholding of information then it can be judged as severely as telling a lie. The omission bias and the omission strategy are closely related.…”
Section: Accountability Related Effectsmentioning
confidence: 99%